Implementasi Bot Whatsapp untuk Layanan Informasi Frontline: Studi Kasus: STMIK Widya Cipta Dharma - Putra, Muhammad Sadam Saktia; Azahari; Pratiwi, Heny (Universitas Methodist Indonesia, 2025)
This study implements a WhatsApp bot as an automated information service at STMIK Widya Cipta Dharma to assist frontline staff tasks. The system was developed using Node.js and the WhatsApp Web API (Baileys Library) with a rule-based matching approach that maps user keywords to predefined responses. The Waterfall method was applied through analysis, design, implementation, and Black Box Testing. The results show that the bot correctly answered 85% of queries and improved information service efficiency by up to 70%.